2013
DOI: 10.1016/j.tox.2013.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Alterations to the circuitry of the frontal cortex following exposure to the polybrominated diphenyl ether mixture, DE-71

Abstract: Recent studies have identified exposure to polybrominated diphenyl ethers (PBDEs) as a risk factor for deficits in cognitive functioning seen in children as well as adults. Additionally, similar alterations in learning and memory have also been observed in animal models of PBDE exposure. However, given these findings, the molecular alterations that may underlie these neurobehavioral endpoints have not been identified. As the frontal cortex is involved in modulating several cognitive functions, the purpose of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 41 publications
3
22
0
Order By: Relevance
“…Specifically, our data demonstrate that BDE 47 and BDE 49 inhibit the early 379 stages of axonal growth in primary cultures of perinatal rat hippocampal neurons. These data 380 extend previous reports demonstrating that commercial PBDE mixture, DE-71, decreases 381 neurite length in primary mouse cortical cultures (Bradner et al, 2013), and that BDE-47 inhibits 382 neurite outgrowth in human embryonic stem cell-derived neurons (Behl et al, 2015), and 383 decreases the length of axons of motor neurons in larval zebrafish (Chen et al, 2012). In our 384 model, exposure to BDE-47 or BDE-49 significantly inhibits axonal growth at concentrations that 385 have no effect on cell viability, indicating that decreased axonal growth is not due to 386 compromised cell viability.…”
Section: Casupporting
confidence: 77%
“…Specifically, our data demonstrate that BDE 47 and BDE 49 inhibit the early 379 stages of axonal growth in primary cultures of perinatal rat hippocampal neurons. These data 380 extend previous reports demonstrating that commercial PBDE mixture, DE-71, decreases 381 neurite length in primary mouse cortical cultures (Bradner et al, 2013), and that BDE-47 inhibits 382 neurite outgrowth in human embryonic stem cell-derived neurons (Behl et al, 2015), and 383 decreases the length of axons of motor neurons in larval zebrafish (Chen et al, 2012). In our 384 model, exposure to BDE-47 or BDE-49 significantly inhibits axonal growth at concentrations that 385 have no effect on cell viability, indicating that decreased axonal growth is not due to 386 compromised cell viability.…”
Section: Casupporting
confidence: 77%
“…They reported decreased levels of the NMDA receptor subunits NR 1 and NR 2 B and of their mRNAs in the hippocampus, which was accompanied by decreased performance in the Morris water maze. In contrast, in young adult mice, a 30 day treatment with DE-71 did not alter NR 2 B levels, but increased expression of vesicular glutamate transporter (Bradner et al 2013b). In another study in rats, prenatal exposure to BDE-99 was shown to increase the activity of the glutamate-nitric oxide-cGMP pathway, as assessed by microdialysis (Llansola et al 2007), possibly as a result of an effect on calmodulin (see below).…”
Section: Potential Mechanisms Of Pbde Developmental Neurotoxicitymentioning
confidence: 84%
“…Alterations in some components of the GABAergic system (e.g. decreases of the GABA-A 2α receptor subunit and the GABA synthesizing enzyme GAD67) have been reported in the cerebral cortex of young adult mice following a 30 day exposure to DE-71 (Bradner et al 2013b). …”
Section: Potential Mechanisms Of Pbde Developmental Neurotoxicitymentioning
confidence: 99%
“…Other biologic mechanisms for neurotoxicity include inducing neuronal apoptosis through oxidative stress, reducing cell migration and differentiation into neurons and oligodendrocytes, interfering with signal transduction, and altering the cholinergic system and neurotransmitter release and function (Costa et al, 2014; Costa and Giordano, 2007; Dingemans et al, 2011; Schreiber et al, 2010). PBDEs may also affect GABAergic and glutamatergic neurotransmitter systems in the frontal cortex (Bradner et al, 2013). Since GABA is a major neurotransmitter in the brain, an imbalance could disrupt the excitation-inhibition neuronal activity and result in deficits in cognitive processes as well as over excitation, hyperactivity, and impulsivity behaviors.…”
Section: Discussionmentioning
confidence: 99%